Risk Factors for CSF/Plasma HIV-1 RNA Discordance in HIV-Infected Patients. (1st October 2022) - Nie, Jingmin; Zeng, Yanming; Zeng, Qingling; Du, Xiang; Chen, Yaokai
Abstract : Background: Few large investigations have evaluated the association of cerebrospinal fluid/plasma (CSF/plasma) discordance with opportunistic neurological infections. We aimed to determine risk factors for CSF/plasma discordance to further assess whether CSF/plasma discordance is associated with antiretroviral therapy (ART) and opportunistic neurological infections. Methods: A retrospective study was conducted based on HIV RNA viral load and associated risk factors in plasma and CSF samples from 491 HIV-infected patients. HIV RNA levels higher in CSF compared with plasma was defined as CSF/plasma discordance. Results: In this study, the rate of CSF/plasma discordance was 18.3%. We observed that headache, cryptococcal antigen, CSF cell count, Treponema pallidum particle assay positivity, and ART use were significantly associated with CSF/plasma discordance in the multivariate logistic regression model. The CSF RNA/plasma RNA ratio was significantly higher in HIV-infected patients with neurological infections than in HIV-infected cases without neurological infections ( P < 0.001). CSF/plasma discordance was significantly different between HIV-infected patients without central nervous system (CNS) infection and those with CNS infection, tuberculous meningitis, cryptococcal meningitis, and neurosyphilis ( P < 0.05). Conclusions: ART and CNS inflammation may influence CSF/plasma discordance.